Crangonidae and Glyphocrangonidae (Decapoda; Caridea) of the Southern Gulf of Mexico - Vázquez-Bader, Ana Rosa; Gracia, Adolfo (Zootaxa, 2013)
Distribution and abundance of species of Crangonidae and Glyphocrangonidae in the Mexican deep-waters of the Gulf of Mexico were analyzed through six research cruises onboard of the R/V Justo Sierra of the Universidad Nacional Autóno-ma de México using an otter trawl in a depth range of 300–1200 m. We collected two and five species of the Crangonidae and Glyphocrangonidae families, respectively. We provide information about its depth and geographic distribution, abun-dance, frequency of occurrence and size structure. Glyphocrangon, composed of five species (G. aculeata, G. alispina, G. haematonotus, G. longleyi and G. spinicauda), was the most common and abundant component during the benthic trawls with a total of 1125 individuals. The family Crangonidae recorded only one genus and two species (Parapontocaris ca-ribbaea and P. vicina) with 21 individuals. A taxonomic key for these crangonid and glyphocrangonid shrimps of the Gulf of Mexico is also provided.